PSYCHOLOGICAL POSSIBILITIES OF THE MANIFESTATION OF MUSICAL ABILITIES IN STUDENTS - Feruza Madrimova. (Scholar Express Journal, 2023)
This article explores the psychological aspects of how musical abilities manifest in students. It discusses the influence of various factors, including talent, motivation, and education, on the development of musical talents. The study employs a multidisciplinary approach, combining insights from psychology, education, and musicology, to offer a comprehensive understanding of this phenomenon
Keywords: Musical abilities; psychological factors; student development